Model to Reduce HIV Related Stigma among Indonesian Nurses - Sismulyanto Sismulyanto; S. Supriyanto; Nursalam Nursalam (International Journal of Public Health Science (IJPHS), 2015)
Stigmatization of persons living with HIV (PLWH) did by health professionals including nurses. Stigma was a barrier of nurses to implement nursing care to PLWH patients. The purpose of this study was to make model of reducing stigma among nurses particularly in the hospital, district of Banyuwangi, Indonesia. Design used in this study was analytical observational. The population was all nurses who worked in 4 hospitals in Banyuwangi of Indonesia. Total sample recruited were 77 respondents. Data were collected by questionnaire and analyzed by using Smart PLS (Partial Least Squares). The result showed that stigma existed among nurses particularly on labelling and stereotyping to PLWH patient. Transcultural components had influence to nurses’ stigma on HIV and AIDS patients; there were jobs factor, facilities factor, values factor, and knowledge factor. Stigmatizing attitudes were found among nurses with quite satisfied. It can be concluded to reduce the stigma of nurses by intervening on transcultural components among other factors affecting jobs factor, facilities factor, values factor and knowledge factor. Further research should apply this model in nursing care.